Parent Involvement – the practice of principals in lower primary schools in Switzerland - Straumann, Martin; Egger, Jan (International Journal about Parents in Education, 2023)
In a project of qualitative social research we analyse the interviews with eight principals of Swiss primary schools. We analyse the attitudes and the practice of parent involvement in these schools, which depend on the socioeconomic status of the community, the professional experience and the actual management style of the school director. We found a great variety of practices that are based on different attitudes on how to interact with parents. We can see a dichotomy of strategies: one is the way how the principals deal with parents who relate to the school to enforce their individual interests in their own child or its success at school. The other one concerns parents who obviously do not cooperate with the school. Patterns of best practice are analysed and will be used as a material to train student teachers. The practice of the principal is not only determined by the parents and the social context of the school. The biographical and the professional experience of the principal, the management style, which means the formation of the school culture and networking in the community, represent an important part of the practice of a principal.